Thermomechanical Analysis of the Effects of Water Distribution on Cracks during Vertical Continuous Casting under Soft Reduction Conditions - Yu Yao; Bo Wang; Shanshan Liu; Liping Zhong; Shiyi Shen; Zheng Chen; Jieyu Zhang (Advances in Materials Science and Engineering)
In the production process of continuous casting slab, the unreasonable secondary cooling system can lead to serious crack defects. This study focuses on the problem of cracks in nuclear power stainless steel produced by vertical continuous casting under soft reduction conditions. Based on the actual production process parameters, the thermomechanical finite element model was established to investigate the effects of water distribution in the secondary cooling zones on cracks by using ProCAST. The results show that the stress concentration is obvious under the original process, especially the positions of 4 mm below the wide surface and 6 mm below the narrow surface. It is easy to generate cracks, and the area with the highest hot-tearing index is approximately 26 cm2. In addition, the secondary cooling system is adjusted based on the existing problems of the original process. The temperature of the casting slab rises by about 15°C at the solidification end point, and the length of the liquid core increases by about 0.5 m when the quantity of the water flow decreases in zone 2 and zone 3. The stress concentration is alleviated, and the possibility of cracking is reduced. Especially, it is evident that the proportion of water on the loose side margin increases from 40% to 45%, while the proportion of water on the fixed side margin of zone 3 is adjusted from 56% to 60%.